1979
DOI: 10.1088/0022-3727/12/5/018
|View full text |Cite
|
Sign up to set email alerts
|

The role of the interfacial layer in Schottky barrier solar cells

Abstract: The interfacial layer in a Schottky barrier solar cell plays an important role in reducing the dark current, which in turn improves the open-circuit voltage and the efficiency of the solar cell. From the transmission of electrons and holes across the interfacial layer the authors have analysed the current mechanism in a Schottky barrier solar cell under two approximations. It is shown that the efficiency of the cell increases at first with the interfacial layer thickness delta , and after acquiring a maximum v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…25 The Schottky barrier is provided by a metal-semiconductor junction. 26,27 Recent theoretical studies, 28,29 along with an earlier experimental study, 30 have suggested that Schottky-barrier solar cells may be a particularly promising proposition if the semiconductor layer (i.e., the absorbing layer) was made from alloys of indium gallium nitride (In ξ Ga 1−ξ N), since the bandgap for these alloys can closely match the range of energies of photons across the entire solar spectrum (i.e., 0.70 to 3.42 eV) by varying the relative proportions of indium and gallium through the parameter ξ ∈ ð0;1Þ. 31 Specifically, indium nitride (i.e., ξ ¼ 1) has a bandgap of 0.7 eV 32,33 and absorbs efficiently across the infrared regime in the solar spectrum, while gallium nitride (i.e., ξ ¼ 0) has a bandgap of 3.42 eV and absorbs efficiently across the near-ultraviolet portion of the solar spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…25 The Schottky barrier is provided by a metal-semiconductor junction. 26,27 Recent theoretical studies, 28,29 along with an earlier experimental study, 30 have suggested that Schottky-barrier solar cells may be a particularly promising proposition if the semiconductor layer (i.e., the absorbing layer) was made from alloys of indium gallium nitride (In ξ Ga 1−ξ N), since the bandgap for these alloys can closely match the range of energies of photons across the entire solar spectrum (i.e., 0.70 to 3.42 eV) by varying the relative proportions of indium and gallium through the parameter ξ ∈ ð0;1Þ. 31 Specifically, indium nitride (i.e., ξ ¼ 1) has a bandgap of 0.7 eV 32,33 and absorbs efficiently across the infrared regime in the solar spectrum, while gallium nitride (i.e., ξ ¼ 0) has a bandgap of 3.42 eV and absorbs efficiently across the near-ultraviolet portion of the solar spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…However, the dye-sensitized solar cells which were prepared from the TiO 2 /Ag electrodes with the Ag nanoparticle sizes bigger than 19.16 nm have low values of the J SC . It is believed that with the Ag particle sizes bigger than 19.16 nm, Schottky barriers formed at the TiO 2 /Ag contacts become dominant and retard electron transport in the conduction bands [1,3,37,38]. Figure 7 plots J SC , V OC , FF, and efficiencies versus the sizes of the Ag nanoparticles.…”
Section: The Effect Of the Ag Nanoparticle Size On Efficiency Of The mentioning
confidence: 99%
“…These problems are exacerbated by p-doping of In ξ Ga 1-ξ N [7]. Solar cells can be designed to use an in-built potential provided by a Schottky-barrier junction, which can occur at a metal/semiconductor interface [8,9]. By partnering n-doped In ξ Ga 1-ξ N with a metal possessing a large work function Φ-as opposed to, say, employing the more usual p-i-n junction-the problems associated with p-doping of the material are avoided.…”
Section: Introductionmentioning
confidence: 99%